Heritability Estimates for Some Growth Traits of Dhatti Camel Breed in Tharparkar - Rameez Raja Kaleri; Hubdar Ali Kaleri; Shahla Karim Baloch; Asma Kaleri; Raza Ali Mangi; Abdul Latif Bhatti; Ghulam Murtaza Mari; Faial Noor Qureshi; Muhammad Saleem Pahnwar; Abdullah Marri (Journal of Basic & Applied Sciences, 2017)
Purposed study was conducted using 12 sire”s 232 offspring. The parameters were studied birth weight, body weight, weight at 6 month, average daily gain to 6 month, yearling weight, total weight gain from 6 month and average daily gain from 6 month till one year. The results for heritability estimates were analyzed using the variance with unequal subclass numbers by using the data of 12 parental half sib groups. The average numbers of offspring were ranged per sire 3 to 84 with mean of 16.4. The effect of sire was observed significantly higher (P≤.0) in said traits. While the results of heritability estimates were observed low to moderate for birth weight, birth weight at 6 month, average daily gain to 6month, yearling weight, total weight, weight gain to 6 month and average daily gain from six month to 1 year respectively. The results for correlation estimates between these traits were positive and high for bwt with TG6 month and bwt at 6 month with and 6 month to 1 year. It is concluded that values for heritability and correlation were observed in range of other farm animal, while for the better production and higher values selection process is advisable for these traits.